PRACTICE OF MECHAOTHERAPEUTIC EXERCISES STIMULATES BRAIN NEUROPLASTICITY IN A POST-ACCIDENT PATIENT BRAIN VASCULAR - Marques Barros, Luciana (Health and Society, 2024)
Cerebrovascular accident (CVA) is a disease that affects motor functionality and quality of life in patients. This article explores the efficacy and safety of physical therapy approaches through the practice of resistance exercises with mechanotherapeutic equipment in post-stroke rehabilitation, analyzing the current literature to provide a comprehensive and grounded view on the subject.